Affirming Cultures, Communities and Experiences: Teaching for Social Justice in Teacher Education Literacy Courses. Issue 1 (4th March 2019) - Howard, Christy Maranda; Ticknor, Anne Swenson
Abstract: In this article we share several activities we use in our teacher education literacy courses that incorporate a social justice lens. For each activity we suggest resources, offer examples we have created and used in our teaching, and share research to support each activity. The activities build on each other, with the intent of increasing preservice teacher knowledge of how to teach for social justice by moving beyond awareness and understanding lived experiences of students to affirming cultures and experiences of all students, creating inclusive and equitable classrooms. By experiencing teaching from this stance in our courses, we hope that our preservice teachers take up and teach from a social justice stance in their future classrooms.